ANALISIS PERHITUNGAN HARGA POKOK PRODUKSI UNTUK MENENTUKAN HARGAJUAL MENGGUNAKAN METODE FULL COSTING PADA UKM SEBLAK WS - Tulus Pujo Nugroho; Abednego Priyatama; Firdaus Ramadhan (Jurnal Ekonomi dan Manajemen, 2022)
The purpose of this study is to determine the cost of production using the full costing method to determine the selling price of SMEs Seblak WS. The method used in this study is the calculation of the cost of production using the Full Costing method, namely determining the cost of a product that takes into account all elements of production costs including raw material costs, direct labor costs, and factory overhead costs, which are fixed or variable. The results of this study are the calculation of the cost of production in determining the selling price using the SME Seblak WS method with the full costing method. So that the results of the calculation of the cost of production produce a difference in selling prices according to UKM Seblak WS with the full costing method which affects the selling price and profit earned by UKM Seblak WS